Social and economic inequality limits disaster prevention amongst the most vulnerable in Vietnam. Issue 1 (4th February 2019) - Chantry, Guillaume; Norton, John
Abstract : Purpose: Vietnam is historically hit by extensive disasters. However, the most vulnerable populations are far from being backed by national/local programmes to reduce disaster impacts on their well-being. In practice, political and socio-economic top-down organisation, channels efforts and limited resources into wealthier parts of the country. The paper aims to discuss these issues. Design/methodology/approach: Learning from 30 years work in Vietnam, this paper presents how "horizontal" solidarity and networking should be promoted and reinforced to really target the needs of vulnerable poor communities. Findings on conditions and challenges are based on practical experience, from family/village level to provincial/national administration, in promoting safe housing and safer communities and in evaluating the barriers for extending and sharing such practices. Findings: Political environments in South East Asian countries become similar to Vietnamese systems, and share a common attitude towards DRR (and CCA): official statements reaffirm the need for DRR at all levels, and the CC threats for local development. But year after year, the situation of marginalised or low-income poor facing disasters does not really see progress. Originality/value: New data collecting methods and technologies are proposed, resilience is quoted as criteria for development, but the major issue remains: how could communities be "at the frontline" when receiving so little "backline" support and resources, compared to benefits from capitalist development shared by only richer parts of society – not concerned in the same way by disasters? The SFDRR in encouraging non-compulsory Civil Society involvement will remain inadequate faced with the increased vulnerability by Vietnam and South East Asian inhabitants.